Metode Latihan Untuk Meningkatkan Kemampuan Bina Diri bagi Anak Tunagrahita Ringan - Rahma Dewinda Yunefi; Elsa Efrina (Universitas Negeri Padang, 2019)
This study discusses how the implementation of learning training methods to improve self-cultivation skills in planting long beans. This study uses qualitative methods with this type of classroom action research. This research uses two cycles, where each cycle has four stages of the process, namely planning, action, observation and reflection. The research is carried out outside the classroom in the form of teacher callaboration as an observer and researcher as the giver of action. The results showed that mentally retardedchildren in the process of cultivating long beans through training methods experienced has increased.